The Strengthening The Role and Function of Library in Supporting Scholarly Communication in The State Islamic Institute of Curup - Rizal, Syamsul; Rodin, Rhoni (Indonesian Journal of Librarianship, 2020)
Problem statement: Libraries have not played an optimal role in supporting Scholarly communication in a university. Purpose: This study aims to analyze the strengthening of the role and function of libraries in supporting Scholarly communication at IAIN Curup. Method: This type of research is descriptive qualitative. Data collection was carried out by means of interviews, documentation and surveys. Result: The results of this study indicate that there are several efforts to strengthen the role and function of libraries including 1) optimizing user education and information literacy activities by adding facilities for these activities; 2) conducting online research skills training for the IAIN Curup academic community; 3) providing e-resources; 4) conducting routine focus group discussions and book reviews. Strengthening the traditional role includes adding to collect quantity and quality, disseminate information, and preserve. Strengthening the role of university libraries in a broader way is through information literacy programs, the materials of which are packaged, expanded and harmonized with the dynamics and scope of Scholarly communication. Conclusion: A library is an integral part of a university, therefore its existence must be strengthened. This strengthening can be done from all aspects, including facilities, human resources, and others. Keywords: library; scholarly communication; IAIN Curup